Managing knowledge processes among the principals and principals of the schools of the privileged and the distinguished from the point of view of the assistants and teachers - Kamel, Jinan Hatem (Al-Adab Journal, 2015)
Assistantteacher: JINAN HATIM KAMIL The current research aiming at identifying Knowledge managementfor he/ she managers of the distinguished male and female schools in Baghdad from assistant and teachers points of view . The difference significance in Knowledge managementfor he/ she managers of the distinguished male and female schools from assistant and teachers points of view. According to the two variations Gender( male- female) Occupation( he/ assistant- she assistant- he/ teacher- she /teachers) and to realize the objectives of the research, a criterion of Knowledge management, the criterion included four scopes which are:- Generating knowledge and measured by (12 items), saving knowledge and measured by (8 items), exchanging knowledge measured by (7 items ), application of knowledge measured by (8 items , and before each item five alternatives for answer which are :-( applied always on him, applied mostly on him, applied on him some times, applied seldom on him, never applied him). And after analyzing the items logically and statistically, and investigation of the measuring characteristics of the criterion, the criterion was applied on the research sample amounted (80 individuals), of( 30 he and she /teachers) and(60 he/she teachers) in the distinguished male and female schools, in Directorates of Baghdad( first, second and third) Baghdad Al-Karkh, and Al-Rusafa(first. Second and third) and then the data were analyzed obtained from the sample statistically, by using (SPSS) and the research has come up with the following results, and would be displayed according to the objectives as follows:- The first objective: the results have showed that mangers of the distinguished schools have knowledge management( generating knowledge, saving knowledge, exchanging knowledge and applying knowledge) from the sample community point of view including he/she assistants and he/she teachers. The second objective:- Sample of assistants: there is no difference among the he/she assistants points of view concerned Knowledge managementin the aspect of (generating knowledge and saving knowledge) for the mangers of the distinguished schools while there was difference statistically denoting of the he/she assistants point of view concerned the Knowledge managementin the aspect of exchanging knowledge for the managers of the distinguished schools , and the difference was infavor of the she/ he assistants’ pointsof view in scope of applying knowledge, and there was any difference statistically denoting in the individuals of the sample points of view of the scientific and humanitarian specializations concerned Knowledge management ( generating knowledge, saving knowledge, exchanging and application of knowledge) for the managers of the distinguished schools. The teachers’ sample:- there is statistically denoting difference in point s of view of he/she teachers in favor of the he/ teachers’ points of view concerned Knowledge management in the two scopes( saving knowledge’s and saving knowledge) for managers of the distinguished schools, and there was no difference statistically denoting in points of view of the individual sample for the scientific and humanitarian specialization concerningKnowledge management (generating knowledge, saving knowledge, exchanging and application of knowledge) for the managers of the distinguished schools